Development of robotic arm and gripper for unmanned ground vehicle in automotive application - Amirul Hafiz, Zexafiza (2021)
Safety rover is an application for a robotic rover to be deployed in hazardous and dangerous condition for human depends in risk situation. In this project, the mechanical components consist of robotic arm, joint and mechanical gripper, backbone chassis and locomotion while electrical components include servo motor, servo controller, a transmitter and a receiver for and wireless controller via USB host for the control system is proposed. Furthermore, it is fitted with a robotic arm to add more versatility to this rover. As the additional information, a robot arm gripper has six degree of freedom (DOF). All these degree of freedom play a fundamental base, shoulders, elbows, waist, wrist and end-effector. It can be used to assist safety authorities to pick object and place it in the desire place and to make search and rescue operations. The project aims to control and safety purpose. In addition, the main objective of this project is to make a simple robotic rover development and production are simple and cost-effective. Equipped with robotic arm integration with real-time vision cameras adds more functions to the rover. This wanderer is the integrated camera on the rover equipped with an FPV camera (“first-person view”) will provide a good view and direction for the rover driver. The proposal will explain the need for suitable, reliable technology and adaptable robotic rover adjusting measures to local conditions can greatly improve worker safety. Therefore, in various tasks, including finding victims, identifying disasters, searching and rescue, surveillance and reconnaissance, and risk assessment, the proposed rover technology can also be used.